DETERMINAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR ANEKA INDUSTRI TAHUN 2019-2020 - Yunika, Amanda; Suhendro; Hendra Titisari, Kartika (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The goal of this research is to ascertain how liquidity, business size, free cash flow, institutional ownership, and profitability affect the dividend policies of companies operating in different industries. Financial reports from several industrial enterprises listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023 served as the study's secondary source of data. Every company listed on the Indonesia Stock Exchange across a range of industries is included in this study. Purposive sampling was used to test nine businesses. Multiple linear regression analysis was used to test the data. The SPSS 21 software was used for the processing. The study demonstrates that institutional ownership and profitability are two elements that affect corporate dividend policy. On the other hand, size, liquidity, and free cash flow have no bearing on the dividend policies of businesses in the miscellaneous industries sector.